Sequence and genome analysis of hepatitis C virus - Hamzah, Hairul Aini (IIUM Press, International Islamic University Malaysia, 2017)
Studying the molecular features of hepatitis C virus (HCV) throws light on its epidemiology and behavior. In this study, HCV infecting a high risk group patient were characterized. The prevalence of the various genotypes and subtypes were determined and the full-length genome of the most prevalent genotype was elucidated. Viral RNA was extracted from sera of 40 HD patients. The molecular technique of reverse-transcription polymerase chain reaction (RT-PCR) was used to detect and amplify segments of the viral genomic RNA at the 5’untranslated region (UTR) and the nonstructural 5B region (NS5B). The base sequences of the amplicons were determined and later employed in phylogenetic analysis for genotype assignment of the isolates. The sequence pattern (SP) and the conformational features of domain III 5’UTR were also evaluated. The overall prevalence of HCV viremia in HD centres was 8.3 %, including one acute infection that occured during the course of study. For 33 of the 40 viremic patients, the HCV 5’UTR and NS5B base sequences were successfully determined. Five patients (15.2 %) were shown to be infected by more than one genotype. In the remaining 28 patients, genotypes 3, 1, 4, and 6 occurred in 19 (67.9 %), seven (25.0 %), one (3.6 %), and one (3.6 %) of them respectively. Four sequence patterns (SPs) were determined in domain III 5’UTR of genotype 3, a finding unique to this genotype. Overall, the secondary structure of the domain was not affected by nucleotide changes in the SP region. The complete base sequence of two genomes of the predominant subtype 3a isolates (MAL 22 & MAL 43) were elucidated and found to be consisting of 9430 and 9429 nucleotides. Genotype 3a HCV genome contained a long open reading frame capable of encoding a sequence of 3010 amino acid residues. In the phylogenetic analysis, both isolates clustered with known HCV-3a isolates (NZL1, K3a & CB), while it diverged from other genotypes by 47.1 - 41.8 %. Three hypervariable regions of the isolates were also revealed and described. The predominance of genotypes 3 and 1 was not unique to HD centres in Pahang as it was reported in normal population in Malaysia. Both the complete viral nucleotide sequence and the amino acid sequence of the coding region of the HCV genome provided the foundation data for future HCV studies in Malaysia including studies on epidemiology, novel diagnostic approaches and antiviral therapies. Despite the known high risk of chronic hepatitis C infection in HD patients, these infections, whether overt or occult and of single or mixed genotypes, were usually clinically silent. Thus, investigational viral nucleic acid based tests on HCV patients was recommended to be done periodically to monitor for the occurrence of these asymptomatic and sometimes even sero-negative infections.